2001
DOI: 10.1097/00003246-200107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prospective trial of high-frequency oscillation in adults with acute respiratory distress syndrome

Abstract: These findings suggest that HFOV has beneficial effects on oxygenation and ventilation, and may be a safe and effective rescue therapy for patients with severe oxygenation failure. In addition, early institution of HFOV may be advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(158 citation statements)
references
References 41 publications
8
144
2
4
Order By: Relevance
“…Some studies of HFOV use for adult ARDS patients with severe hypoxemia and high plateau airway pressures have verified significant improvement in oxygenation and suggest that early initiation may have better outcomes. 3,4,19 It has also been shown that HFOV is effective and safe in correcting oxygenation failure associated with ARDS in surgical patients. 20 In this severe TRALI case, severe hypoxemia persisted despite pressure control ventilation support with 100% oxygen and PEEP of 18 cm H 2 O for 12 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies of HFOV use for adult ARDS patients with severe hypoxemia and high plateau airway pressures have verified significant improvement in oxygenation and suggest that early initiation may have better outcomes. 3,4,19 It has also been shown that HFOV is effective and safe in correcting oxygenation failure associated with ARDS in surgical patients. 20 In this severe TRALI case, severe hypoxemia persisted despite pressure control ventilation support with 100% oxygen and PEEP of 18 cm H 2 O for 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies have shown improved oxygenation in patients with refractory hypoxemia. 3,4 A recent Cochrane review concluded that HFOV may be a rescue therapy for improving survival in ARDS patients. 5 Herein is a case of TRALI with persistent hypoxemia under pressure-control ventilation mode with 100% oxygen, low tidal volume, and high PEEP.…”
Section: Introductionmentioning
confidence: 99%
“…Many have simply recommended setting mean airway pressure equal to or a few centimeters of H 2 O above that used during CV (23)(24)(25). Goddon et al (26), in a 28 ± 5− kg lavage-injured sheep model investigated the use of the pressure-volume (P-V) curve to set mean airway pressure during HFO.…”
Section: Setting Of Mean Airway Pressurementioning
confidence: 99%
“…In this case high frequency oscillatory ventilation (HFOV) represents a rescue therapy. (1,2) It is an alternative technique of ventilation in which small tidal volumes (1-4 mL/kg) are delivered at high frequencies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Hz) with an oscillatory pump. (3) There are some studies and case reports in the literature of successful use of HFOV in acute respiratory distress syndrome (ARDS) of non-traumatic aetiology (4-7) however its use in trauma patients is limited.…”
Section: Introductionmentioning
confidence: 99%